Direct Neuronal Reprogramming Reveals Unknown Functions for Known Transcription Factors - Colasante, Gaia; Rubio, Alicia; Massimino, Luca; Broccoli, Vania (Frontiers in Neuroscience, 2019)
In the recent years, the need to derive sources of specialized cell types to be employed in cell replacement therapies and modeling studies has triggered a fast acceleration of novel cell reprogramming methods. In particular, in neuroscience a number of protocols for the efficient differentiation of somatic or pluripotent stem cells have been established to obtain a renewable source of neurons. Alternatively, several neuronal populations have been generated through direct reprogramming/transdifferentiation, that concerns the conversion of fully differentiated somatic cells into neurons. This is achieved through the forced expression of selected transcription factors (TFs) in the donor cell population. The reprogramming cocktail is chosen after an accurate screening process involving lists of TFs characteristic of the desired cell lineage. In some instances, this line of studies has revealed the crucial role of TFs whose function in the differentiation of a given specific cell type had been neglected or underestimated. Herein, we will speculate on how the in vitro studies have served to better understand some mechanisms of physiological neuronal development in vivo, highlighting inherent examples of direct cell reprogramming methodologies.